The Influence of Learning Motivation, Interest in Learning, Self Confidence on Learning Outcomes with Cognitive Ability as Moderation - Risdiantoro, Galih; Rahmawati, Rini (Universitas Syiah Kuala, 2024)
This research aims to determine and analyze the influence that occurs between the variables of Learning Motivation, Interest in Learning, and Self-Confidence, which have a significant influence on student learning outcomes moderated by the Cognitive Ability of National Police Non-Commissioned Officer students at the State Police School (SPN) of the South Kalimantan Regional Police (Polda). The research method used a questionnaire with 42 National Police non-commissioned officers as the sample.